Gentiopicroside activates the bile acid receptor Gpbar1 (TGR5) to repress NF-kappaB pathway and ameliorate diabetic nephropathy. (January 2020) - Xiao, Haiming; Sun, Xiaohong; Liu, Renbin; Chen, Zhiquan; Lin, Zeyuan; Yang, Yan; Zhang, Meng; Liu, Peiqing; Quan, Shijian; Huang, Heqing
Graphical abstract: Highlights: Gentiopicroside reversed the downregulation of TGR5 and the upregulation of ECM and inflammatory factors in HG-induced GMCs. Gentiopicroside inhibited the activation of the NF-κB signalling pathway by preventing the phosphorylation of IκBα. The depletion of TGR5 blocked the inhibition of the NF-κB signalling pathway by GPS. Gentiopicroside enhanced the interaction between β-arrestin2 and IκBα via TGR5 activation. Abstract: Our previous studies indicated that the G-protein-coupled bile acid receptor, Gpbar1 (TGR5), inhibits inflammation by inhibiting the NF-κB signalling pathway, eventually attenuating diabetic nephropathy (DN). Gentiopicroside (GPS), the main active secoiridoid glycoside of Gentiana manshurica Kitagawa, has been demonstrated to inhibit inflammation in various diseases via inhibiting the inflammatory signalling pathways. However, whether GPS inhibits the NF-κB signalling pathway by activating TGR5 and regulates the pathological progression of diabetic renal fibrosis requires further investigation. In this study, we found that GPS significantly reversed the downregulation of TGR5 and inhibited the overproduction of fibronectin (FN), transforming growth factor β1 (TGF-β1), intercellular adhesion molecule-1 (ICAM-1) and vascular adhesion molecule-1 (VCAM-1) in glomerular mesangial cells (GMCs) exposed to high glucose (HG). Additionally, GPS prevented the phosphorylation and degradation of IκBα, and subsequently inhibited the activation of the NF-κB signalling pathway. Further investigation found that GPS enhanced the stabilization of IκBα by promoting the interaction of β-arrestin2 with IκBα via TGR5 activation, which contributed to the inhibition of NF-κB signalling pathway. Importantly, the depletion of TGR5 blocked the inhibition of the NF-κB signalling pathway and reversed the downregulation of FN, ICAM-1, VCAM-1 and TGF-β1 by GPS in HG-induced GMCs. Moreover, GPS increased the TGR5 protein levels and promoted the interaction between IκBα and β-arrestin2, thereby inhibiting the reduction of IκBα and blocked NF-κB p65 nuclear translocation in the kidneys of STZ-induced diabetic mice. Collectively, these data suggested that GPS regulates the TGR5-β-arrestin2-NF-κB signalling pathway to prevent inflammation in the kidneys of diabetic mice, and ultimately ameliorates the pathological progression of diabetic renal fibrosis.